2006
DOI: 10.7863/jum.2006.25.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficiency of Using Second-Trimester Nasal Bone Hypoplasia as a Single or a Combined Marker for Fetal Aneuploidy

Abstract: ,"Evaluating the efficiency of using second-trimester nasal bone hypoplasia as a single or a combined marker for fetal aneuploidy."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
3
24
1
3
Order By: Relevance
“…Using a combination of markers in NB assessments improves the detection of Down syndrome [27]. Previous researches suggest that race and ethnicity significantly affect the expected NBL in the second trimester, indicating the need to establish formulas for estimating NBL that are specific to different races and ethnicities [13].…”
Section: Discussionmentioning
confidence: 98%
“…Using a combination of markers in NB assessments improves the detection of Down syndrome [27]. Previous researches suggest that race and ethnicity significantly affect the expected NBL in the second trimester, indicating the need to establish formulas for estimating NBL that are specific to different races and ethnicities [13].…”
Section: Discussionmentioning
confidence: 98%
“…These studies have shown that some second trimester Down syndrome fetuses do have an apparent absence of the nasal bone whereas others show hypoplasia relative to unaffected fetuses. [2][3][4][5][6][7][8][9] Both the use of MoM and biparietal diameter/ nasal bone ratios seem to provide practical approaches to screening for fetal Down syndrome, because we were unable to demonstrate any significant difference between the two methods. The various studies that have used biparietal diameter/nasal bone ratios have reported widely different sensitivities and specificities for same cutoff (5-7, this study).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of other makers with the NB assessment was associated with an improvement in detecting the risk of Down syndrome [27]. Thus, there is a need to establish the specific evaluated formulas by NBL with different methods.…”
Section: Discussionmentioning
confidence: 99%